A comparison of brain MRI outcomes in youth american football versus noncontact sport athletes - Ichesco, E. Li, Y.; Shih, C.-H.; Ichesco, I.; Almeida, A.; Varangis, E.; Schrepf, A.; Kaplan, C.; Popovich, M.; Peltier, S. J.; Harris, R. E.; Lorincz, M. T.; He, X.; et al. (Medicine & Science in Sports & Exercise, 2026)
Objectives: